How do public health practitioners in China perceive injury prevention? A survey. Issue 3 (28th June 2013) - Tan, Aichun; Zhang, XiaoTao; Baker, Susan P; Hu, Guoqing
Abstract : To report public health practitioners' perceptions of injury prevention in Changsha, China. We undertook a cross-sectional study at Changsha, Hunan, China. An anonymous self-reported survey was conducted to ascertain the proportion of respondents who answered negatively to questions about the value of injury prevention. Over 20% of respondents answered 'unpreventable' or 'don't know' to whether injuries from natural environmental disaster, homicide/assault, poisoning, animal bite, cut/pierce, suffocation and electric current were preventable. More than 40% of respondents answered 'no' or 'don't know' to whether the prevention of injuries from homicide/assault, cut/pierce, fall, suicide/self-harm, drowning, road traffic crash and fire/burn belonged to the job of public health. Only 48% of respondents supported building a division/office within the Centers for Disease Control and Preventions at all levels. Many public health practitioners in Changsha had misperception about injury prevention. Education and training are needed to correct their misperception.